Average Error: 1.0 → 0.1
Time: 16.5s
Precision: 64
\[\cosh \left(x + 1\right) - \cos 1\]
\[\left(\sqrt[3]{\cosh \left(x + 1\right) - \cos 1} \cdot \sqrt[3]{\sqrt{\cosh \left(x + 1\right) - \cos 1} \cdot \sqrt{\cosh \left(x + 1\right) - \cos 1}}\right) \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos 1}\]
\cosh \left(x + 1\right) - \cos 1
\left(\sqrt[3]{\cosh \left(x + 1\right) - \cos 1} \cdot \sqrt[3]{\sqrt{\cosh \left(x + 1\right) - \cos 1} \cdot \sqrt{\cosh \left(x + 1\right) - \cos 1}}\right) \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos 1}
double f(double x) {
        double r14198286 = x;
        double r14198287 = 1.0;
        double r14198288 = r14198286 + r14198287;
        double r14198289 = cosh(r14198288);
        double r14198290 = cos(r14198287);
        double r14198291 = r14198289 - r14198290;
        return r14198291;
}

double f(double x) {
        double r14198292 = x;
        double r14198293 = 1.0;
        double r14198294 = r14198292 + r14198293;
        double r14198295 = cosh(r14198294);
        double r14198296 = cos(r14198293);
        double r14198297 = r14198295 - r14198296;
        double r14198298 = cbrt(r14198297);
        double r14198299 = sqrt(r14198297);
        double r14198300 = r14198299 * r14198299;
        double r14198301 = cbrt(r14198300);
        double r14198302 = r14198298 * r14198301;
        double r14198303 = r14198302 * r14198298;
        return r14198303;
}

Error

Bits error versus x

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 1.0

    \[\cosh \left(x + 1\right) - \cos 1\]
  2. Using strategy rm
  3. Applied add-cube-cbrt0.1

    \[\leadsto \color{blue}{\left(\sqrt[3]{\cosh \left(x + 1\right) - \cos 1} \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos 1}\right) \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos 1}}\]
  4. Using strategy rm
  5. Applied add-sqr-sqrt0.1

    \[\leadsto \left(\sqrt[3]{\color{blue}{\sqrt{\cosh \left(x + 1\right) - \cos 1} \cdot \sqrt{\cosh \left(x + 1\right) - \cos 1}}} \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos 1}\right) \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos 1}\]
  6. Final simplification0.1

    \[\leadsto \left(\sqrt[3]{\cosh \left(x + 1\right) - \cos 1} \cdot \sqrt[3]{\sqrt{\cosh \left(x + 1\right) - \cos 1} \cdot \sqrt{\cosh \left(x + 1\right) - \cos 1}}\right) \cdot \sqrt[3]{\cosh \left(x + 1\right) - \cos 1}\]

Reproduce

herbie shell --seed 1 
(FPCore (x)
  :name "cosh(x+1)-cos(1)"
  (- (cosh (+ x 1.0)) (cos 1.0)))